2009
DOI: 10.1093/alcalc/agn109
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Neurogenesis from Neural Progenitor Cells Isolated from the Hippocampus Region of the Brain of Adult Rats Exposed to Ethanol during Early Development through Their Alcohol-Drinking Mothers

Abstract: Neuronal maturation was significantly delayed in ethanol-exposed rats. AC(o) NPCs, up to day 7 of culture, exhibited high beta-catenin-probe binding, an increase in Ca(2+) when exposed to gamma-amino butyric acid (GABA) and lack of response to glutamate (Glu) exposure. beta-Catenin-probe binding and the stimulatory effects of GABA declined thereafter. AC(o) NPCs, at culture day 29, exhibited high beta-catenin-probe binding, lack of response to GABA and elevated Glu-induced increase in Ca(2+i). Cultures of AE(o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 89 publications
6
30
0
Order By: Relevance
“…This may be secondary due to the commensurate loss of BMP activity, although acute ethanol can also rapidly deplete nuclear β-catenin from osteoblasts (Chen et al 2010), a finding consistent with our own studies with neural crest progenitors. For neurons the findings are contradictory, with chronic ethanol exposure reducing the total β-catenin content of cultured hippocampal neurons (Singh et al 2009) but elevating β-catenin in the frontal cortex of chronic alcoholics (Al-Housseini et al 2008). These neuronal studies did not distinguish between the cytoskeletal and nuclear pools and thus the functional consequences of those changes are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…This may be secondary due to the commensurate loss of BMP activity, although acute ethanol can also rapidly deplete nuclear β-catenin from osteoblasts (Chen et al 2010), a finding consistent with our own studies with neural crest progenitors. For neurons the findings are contradictory, with chronic ethanol exposure reducing the total β-catenin content of cultured hippocampal neurons (Singh et al 2009) but elevating β-catenin in the frontal cortex of chronic alcoholics (Al-Housseini et al 2008). These neuronal studies did not distinguish between the cytoskeletal and nuclear pools and thus the functional consequences of those changes are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important to mention that levels of neurogenesis are permanently affected also by other ELS not necessarily related to the mother-infant interaction alone. For example, ELS inflammation (Jakubs et al 2008;Musaelyan et al 2014), radiation therapy (Fukuda et al 2005;Naylor et al 2008;Hoffman and Yock 2009), anesthesia (Zhu et al 2010), stroke (Spadafora et al 2010), infection (Bland et al 2010), and ethanol exposure (Singh et al 2009) induce long-lasting effects on neurogenesis associated with late-onset cognitive impairment. Thus, the studies described have shown that EL experiences during both pre-and postnatal development can bidirectionally alter hippocampal neuronal plasticity and synaptic integrity.…”
Section: Long-lasting Effects Of Perinatal Stress Exposurementioning
confidence: 99%
“…They observed reduced neurite branching and increased primary neurite length in ethanol-pretreated differentiating neurons in the proliferative phase [Camarillo et al, 2008]. Most recently, Singh et al [2009] described several molecular changes in neurogenesis found in embryonic rodents exposed to alcohol. The focus of the study was on Wnt-␤ -catenin and its role in ethanol-induced changes in neurogenesis.…”
Section: Alcohol As a Teratogenmentioning
confidence: 99%